Magnitude and Determinants of Immediate Adverse Neonatal Outcomes Among Babies Born by Cesarean Section in Public Hospitals in Harari Region, Eastern Ethiopia - Abdullahi YY; Assefa N; Roba HS (Dove Medical Press, 2021)
Yasir Younis Abdullahi,1 Nega Assefa,2 Hirbo Shore Roba3 1Department of Obstetrics and Gynecology, Jegula Hospital, Harar, Ethiopia; 2College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3Department of Public Health, Haramaya University, Harar, EthiopiaCorrespondence: Yasir Younis AbdullahiJegula Hospital, Harar, EthiopiaTel +251930340123Email yasdire@gmail.comPurpose: To determine the magnitude and determinants of immediate adverse neonatal outcomes among babies born by cesarean section in public hospitals in the Harari region, Eastern Ethiopia.Patients and Methods: A prospective follow-up study among 715 eligible babies born by cesarean section in Jegula and Hiwot Fana public hospitals in Harar. Neonate is said to have immediate adverse outcomes if one of the following were detected: (1) baby died, or (2) admitted to NICU, or (3) its primitive reflexes were absent within 24 hours after delivery Adjusted risk ratios (ARRs) and 95% confidence intervals (CIs) were computed using modified Poisson regression.Results: During the follow-up period, a total of 44 babies died, 139 admitted to NICU, and 133 had absent neonatal reflexes. In general, 157 had an adverse neonatal outcome after CS. The following conditions were postively and statistically related with the outcome: estimated household income (ARR 2.19 CI 1.57– 3.07), having no Antenatal care (ARR 1.46 1.08– 1.97), history of medical or obstetric condition (ARR 1.78 CI 1.38– 2.31, having an absolute indication for delivery (ARR 1.71 CI 1.28– 2.29), presence of meconium (ARR 1.61 CI 1.22– 2.12), low birth weight (ARR 1.96 CI 1.42– 2.70), and respiratory depression at birth (ARR 2.50 CI 1.80– 3.48).Conclusion: A fifth of babies developed immediate adverse outcomes after a cesarean section. Several maternal clinical factors were predictors for immediate adverse neonatal outcomes. Assessing previous clinical and obstetric conditions of the women during ANC would help properly plan in averting the occurrence of immediate adverse neonatal outcomes after birth.Keywords: a follow-up study, neonatal mortality, NICU admission rate, absent neonatal reflexes, adverse neonatal outcomes